INFECTIONS TRANSMITTED FROM MOTHER TO NEWBORN AND THEIR EFFECTS ON NEONATAL OUTCOMES - Ahmadjonova Robiyakhon Abdumutallib qizi (Western European Studies, 2025)
This review explores the mechanisms of vertical transmission, clinical features, diagnostics, and treatment of these infections. It highlights how pathogens such as cytomegalovirus, toxoplasmosis, rubella, herpes simplex virus, and severe acute respiratory syndrome coronavirus 2 affect neonatal outcomes, causing congenital anomalies, preterm birth, growth restriction, and even death. Evidence shows that early detection, timely antimicrobial therapy, and maternal screening can greatly reduce adverse outcomes. The review offers evidence-based recommendations and outlines future research priorities, underscoring the importance of integrated maternal-fetal care to improve neonatal health
Keywords: vertical transmission; congenital infections; neonatal outcomes